2014
DOI: 10.1002/adma.201305708
|View full text |Cite
|
Sign up to set email alerts
|

Moisture‐Activated Torsional Graphene‐Fiber Motor

Abstract: A new type of moisture-driven rotational motor is developed using a helical arrangement of graphene sheets along a graphene oxide fiber, which not only presents remarkable performance as a reversible rotary motor with a rotary speed of up to about 5200 revolutions per minute under humidity alternation, but also allows the construction of humidity switches and promising moisture-triggered electric generators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
296
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(298 citation statements)
references
References 23 publications
2
296
0
Order By: Relevance
“…For instance, large-diameter, wax-filled yarns made from niobium nanowires have been demonstrated to torsionally actuate by up to 12°/mm when electrically heated (47). Similar to water-absorbing CNT yarns, Cheng et al used twisted graphene oxide fibers to absorb water, delivering up to 5,190 rpm during torsional actuation (48). More recently, CruzSilva et al demonstrated graphene-oxide fibers that can be twisted, knotted, and coiled (49), potentially opening the path to tensile actuation from graphene fibers.…”
Section: Emerging Types Of Twisted Musclesmentioning
confidence: 99%
“…For instance, large-diameter, wax-filled yarns made from niobium nanowires have been demonstrated to torsionally actuate by up to 12°/mm when electrically heated (47). Similar to water-absorbing CNT yarns, Cheng et al used twisted graphene oxide fibers to absorb water, delivering up to 5,190 rpm during torsional actuation (48). More recently, CruzSilva et al demonstrated graphene-oxide fibers that can be twisted, knotted, and coiled (49), potentially opening the path to tensile actuation from graphene fibers.…”
Section: Emerging Types Of Twisted Musclesmentioning
confidence: 99%
“…However, both of the two types of sensors cannot be used as flexible sensors due to the complicated measurement systems and nonflexible active materials. In addition to the above, other types of humidity sensors based on the change of impedance, voltage, or strain, have been reported [164][165][166].…”
Section: Flexible Humidity Sensorsmentioning
confidence: 94%
“…(C) Kinematics of hygroresponsive actuators with perpendicular and oblique reinforcement [53] 它方向上的分子将发生膨胀. 样品的平行取向会引起材 料在垂直方向的收缩或膨胀 [101] . …”
Section: (B)可形状转变的水mentioning
confidence: 99%